تفكير الأدب الإسلاميّ المعاصر في الدول العربيّة: نشأته وبواكير أعلامه وحقيقته: Thought of Modern Islamic Literature in Arab Countries: Its Emergence, Pioneers, and Concept - Musling, Mohd Nizwan; Samah, Rosni (‘Abqari Journal, 2024)
The study aims to investigate the origins of Modern Islamic Literature (MIL) thinking among Arab pioneers and their efforts in revealing the features of this literature. The study employed the historical inductive method by tracing the pioneers’ works and studies that dealt with the MIL. One of the most important findings of this study is Ali Al-Nadawi started the thinking of MIL. Then Sayyid Qutb in 1952 initiated this idea and strongly advocated it through his article entitled “Manhaj al-Adab”. Then his brother Muhammad Qutb continued this effort through his book, “Manhaj al-Adab al-Islamiy”, explaining the opinions and issues raised by Sayyid Qutb until this book is considered as the first book in the Arabic language addresses the literary problems in the light of Islam. This call continued until the MIL is defined as the beautiful expression of the universe, life, human and the Creator through Islam’s worldview. It has its formal technical characteristics, which are the correct word that inspires the Islamic spirit, the tight style and precise systems. In contrast, the intrinsic characteristics consist of the idea and the emotion that build on the Islamic worldview of the universe, life, human and the Creator. يهدف هذا البحث إلى الكشف عن نشأة تفكير الأدب الإسلاميّ المعاصر لدى رواده من العلماء العرب، ثم إبراز مجهوداتهم في تجلية معالم هذا الأدب. ويتكأ البحث على المنهج الاستقرائيّ التاريخيّ بتتبّع مؤلَّفات الرواد في هذا الحقل المعرفيّ، والدراسات التي تناولت الأدب الإسلاميّ المعاصر. ومن أهمّ ما توصَّل إليه البحث أنَّ تفكير الأدب الإسلاميّ المعاصر قد بدأ على يد علي الندوي. ثم بادر سيد قطب إلى هذه الفكرة ودعا إليها بقوةٍ خلالَ مقالته بعنوان "منهج الأدب" التي صدرت سنة 1952. ثم واصل هذا الجهدَ أخوه محمّد قطب من خلال كتابه "منهج الفن الإسلاميّ"، موضِّحاً فيه الآراء والقضايا التي أثارها سيد قطب حتى يعدّ هذا الكتاب أوّل كتابٍ باللغة العربية يُعالج القضايا الأدبيّة في ضوء الإسلام. وتعاقبت هذه الدعوة حتى يتحدَّد تعريف الأدب الإسلاميّ المعاصر بأنه التعبير الجميل عن الكون والحياة والإنسان والخالق من خلال تصوُّر الإسلام لها. وله خصائص فنية شكليّة تتمثّل في الكلمة الصحيحة الموحية بالروح الإسلاميّة، والأسلوب المحكم والنظم الدقيق. وأما خصائصه الجوهريّة فهي تتألَّف من الفِكرة والعاطفة تبنيان على التصوّر الإسلاميّ للكون، والحياة، والإنسان، والخالق.